Proportional Hazard Regression Analysis By Using Survival Data - Wan Muhamad Amir Bin W Ahmad; Norizan Mohamed; Zurairah Ahmad; Mustafa bin Mamat (Program Studi Statistika Unisba, 2005)
Recently a number of papers have considered both longitudinal changes in a variable and theassociated effect on the length of time to the occurrence of an event (Schork and Remington, 2003).Longitudinal research is performed to study a phenomenon as it is evolving over time. Thephenomenon will generally show changes over time, but it may also show stability. Researchers inpsychology often use longitudinal designs to assess change. Various statistical techniques have beenused to analyze these data, including proportional hazard regression. This paper illustrates the use ofthe SPSS to examine blood data with this technique, as well. The advantages of using a Cox modelapproach to blood pressure analysis are discussed.